Stakeholder engagement in the development of edutourism at the Sekolah Sungai Siluk Bantul District - Ahdiyana, Marita; Septiningrum, Lutfia; Fitriana, Kurnia Nur; Anggalini, Titis Dewi; Jonga, Ebrima (Universitas Negeri Yogyakarta, 2025)
Researchers typically focus on the participation of stakeholders who cannot influence the organisation. This right requires a more effective perspective on participation and leads to the granting of power. This research investigates how extensively stakeholders have participated in developing educational tourism at Bantul Regency's Siluk School River. This investigation uses a case study approach and employs descriptive qualitative methods. Researchers gathered the data through observation and conducted in-depth interviews with relevant informants for the study. Researchers gather relevant documents by conducting a literature search to collect data. The researchers conducted qualitative data analysis continuously and thoroughly in an interactive manner. The results showed stakeholders actively developed educational tourism at the Siluk School River. PT PLN contributes to infrastructure development through its corporate social responsibility program. The Selopamioro Village Government actively supports and collaborates with the community's activities. Various communities, universities, and non-governmental organisations actively contribute to community empowerment activities. However, other government institutions, like local governments, still lack clearly defined functions.